Relevansi Pendidikan Dengan Ajaran Upanisad (Pandangan Stoikisme) - I Gede Herman Saputra; Putu Sukariawan (Pramana: Jurnal Hasil Penelitian, 2023)
Upanisad is one of the sections of the Holy Book of the Weda which belongs to the Sruti section, where the Upanishad is considered to be the oldest part of Weda. Stoicism is one of the current Western philosophies that teaches the importance of self-control and emotional calm. Specifically, this article deals with education in the past, present and future times and Stoicism as its bridge. As for the methodology used in this writing is the study of intertexts where the study in this research through the writing that has circulated. There is no sloka Upanisad that directly connects the teachings of Upanishad with Stoic philosophy. There are several concepts in the teachings of Upanisad that have similarities with the principles adopted by the Stoics. In the teachings of Upanisad there is a concept of the importance of self-control and the development of deep consciousness. This is similar to the Stoic view that emphasized self-control and strong character development. The Upanisad is one of the sacred texts in Hinduism and is part of the Weda sacred book. Education in the Upanisad era was based on the close relationship between teacher and student. Education in the Upanisad era was not limited to pure academic learning, but emphasized more on spiritual, existential understanding, and the achievement of spiritual liberation. Meditation and contemplation are used as tools to deeper understanding.